2021
DOI: 10.3389/fpsyg.2021.781521
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Interindividual Differences, Expectations and Placebo and Nocebo Effects in Itch

Abstract: Introduction: Placebo and nocebo effects are positive and negative health outcomes that can be elicited by the psychosocial context. They can be mediated by expectations, and may emerge in somatic symptoms even when people are aware of these effects. Interindividual differences (e.g., in personality, affective states) could impact placebo and nocebo responding, but findings are inconsistent.Methods: The current work examined expectation as a mediator of the association between verbal placebo and nocebo suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 85 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…For instance, a patient with chronic back pain seeks treatment from an Ayurvedic practitioner who prescribes herbal remedies, dietary changes, mindfulness meditation, and positive affirmations (Torstensen, T. A. (1996); Ondrejkovicova, A., Petrovics, G., Svitkova, K., & Balogh, V. (2017); S, M., Wele, A., Patgiri, B. J., & Porszasz, PLACEBO/NOCEBO EFFECT CATEGORIES FROM EASTERN AND WESTERN PERSPECTIVES mechanisms, and past experiences (Bagarić et al, 2022;Meeuwis et al, 2021). These factors can influence an individual's susceptibility to negative expectations thereby associating themselves leading to classical conditioning leading to indirect-direct appearance of classical conditioning (refer 4).…”
Section: Further Insights Into Placebo-nocebo Effectmentioning
confidence: 99%
“…For instance, a patient with chronic back pain seeks treatment from an Ayurvedic practitioner who prescribes herbal remedies, dietary changes, mindfulness meditation, and positive affirmations (Torstensen, T. A. (1996); Ondrejkovicova, A., Petrovics, G., Svitkova, K., & Balogh, V. (2017); S, M., Wele, A., Patgiri, B. J., & Porszasz, PLACEBO/NOCEBO EFFECT CATEGORIES FROM EASTERN AND WESTERN PERSPECTIVES mechanisms, and past experiences (Bagarić et al, 2022;Meeuwis et al, 2021). These factors can influence an individual's susceptibility to negative expectations thereby associating themselves leading to classical conditioning leading to indirect-direct appearance of classical conditioning (refer 4).…”
Section: Further Insights Into Placebo-nocebo Effectmentioning
confidence: 99%
“…12 An additional analysis of previous trials (Studies 8, 9 and 11; Table 2) was conducted by S. Meeuwis et al, and published in 2021. 13 Innovative statistical methods were applied to determine the interindividual differences on how placebo effects are formed. 13 The researchers reported that the effects of open-label positive and negative verbal suggestions on itch may be more dependent on its expectation, while the closed label approach would directly influence the itch.…”
Section: Excludedmentioning
confidence: 99%
“…13 Innovative statistical methods were applied to determine the interindividual differences on how placebo effects are formed. 13 The researchers reported that the effects of open-label positive and negative verbal suggestions on itch may be more dependent on its expectation, while the closed label approach would directly influence the itch. 13 Furthermore, the researchers determined that low sensitivity to rewards and high ignorance of bodily signals were associated with increased placebo response to verbal suggestion.…”
Section: Excludedmentioning
confidence: 99%
See 1 more Smart Citation
“…Such outcomes were described by Hahn as nocebo effects ( Hahn, 1997 ), which were distinguished from ‘placebo side effects’, whereby a treatment primarily intended as beneficial can cause harmful outcomes. This is the case of nocebo side effects, namely, unpleasant symptoms that arise following a treatment that is primarily intended as beneficial, but of which specific side effects are anticipated ( Meeuwis et al, 2021 ). Notably, recent evidence suggests that primary manipulations of nocebo and nocebo side effects do not produce equivalent results.…”
Section: Introductionmentioning
confidence: 99%